ANALISIS PENGARUH BOOK TO MARKET EQUITY, FIRM SIZE, MARKET VALUE ADDED (MVA), MOMENTUM, DAN TRADING VOLUME TERHADAP RETURN SAHAM (Studi Kasus Perusahaan Yang Terdaftar Dalam Indeks LQ-45 Periode 2012 s/d 2016) - Kosasi, Aldi; Prasetiono, Prasetiono (Faculty of Economics and Business Diponegoro University, 2017)
The purpose of stock investing is to seek profit in the future. This research was conducted in order to examine the influence of book to market equity, firm size, market value added (MVA), momentum, and trading volume on stok return.Â Sample of this study used companies that registered on Indonesia Stock Exchange during 2012-2016.This research was made because there are differences in results between studies with each other. The sampling technique used in this research is purposive sampling method covering 24 companies as samples. The analysis used multiple regression, which is preceeded by a test consisting of the classical assumption test for normality, multicollinearity test, heteroscedasticity test and autocorrelation test. Hypothesis testing is using F test and t test. The result of this research show that book to market equity had significant negative effect on stock return as well as trading volume variable had significant positive effect on stock return. In addition, the results did not support that firm size, market value added (MVA) and momentum significant effect on stock return. Moreover it found that the value of the adjusted R square is 19,1%. This means that 80,9% is explained by other variables outside the model